Effort For The Development of Islamic Religion For Prisoners of Sidoarjo Prices: Upaya Pembinaan Agama Islam Untuk Narapidana Lapas Sidoarjo - Handy Ichwan Suwandono; Dzulfikar Akbar Romadlon (Universitas Muhammadiyah Sidoarjo, 2022)
The program for implementing Islamic religious development at the Sidoarjo Prison is one method for fostering and educating inmates. So in this prison the coaching is carried out every day with good management and aims to add diversity in students or prisoners if their bad deeds are very detrimental and create a sense of Inconvenient for the community. And from this explanation, the author takes 2 problem formulations, including: How are the programs and implementations in the implementation of Islamic religious development for prisoners at the Sidoarjo Prison and What are the obstacles and supporters in the implementation of Islamic religious development for prisoners at the Sidoarjo Prison? This research uses descriptive qualitative research. After that, the next result is the thing that becomes an obstacle or obstacle and supporting aspect in the coaching process is the lack of human resources in the implementation of Islamic religious development programs and by cooperating with mass organizations and other institutions in order to assist the process of implementing prisoner development.